Innovation and Advanced Technology Use in the Canadian Forest Sector - Kollarova, Sona (Université d'Ottawa / University of Ottawa, 2014)
The forest sector is traditionally viewed as stagnant and non-innovative in comparison to higher-value added industries. The sector is being challenged by environmental, market and consumer changes at home and internationally. To combat these challenges, forestry firms must undergo a transformation in their activities, including their production methods by producing innovative and sustainable products and materials. This involves investing in innovation, advanced technologies and new products. The purpose of this study is to understand the impact of adoption of advanced manufacturing technologies on firm performance in the Canadian forest sector. The study is based on data from the 2007 Survey of Advanced Technology and interviews with technology adopters. The differences between technology adopters and non-adopters in terms of capital investment, R&D, training, management practices and innovation were analyzed. The findings suggest that the adoption of advanced technologies is important for the realizations of innovations. Firms which were both innovative and adopted technology were most likely to report improvements in performance post-adoption.
Keywords: Innovation; Management; Technology Adoption